Spatial and temporal variations in subsidence due to the natural consolidation and compaction of sediment in the yellow river delta, china. Issue 2 (7th February 2019) - Zhang, Yi; Huang, Haijun; Liu, Yilin; Liu, Yanxia; Bi, Haibo
ABSTRACT: The Yellow River Delta, which is the second-largest delta in China, has experienced varying degrees of land subsidence since the late 1970s. Although recent studies have identified the natural consolidation and compaction of sediment among the most important contributors to geologic processes, their processes have rarely been quantified. We estimated the sediment compaction over different time ranges to determine the temporal evolution of subsidence parameters (i.e., cumulative compaction). Estimates of primary consolidation, secondary consolidation, and the degree of consolidation in 152 boreholes revealed the spatial–temporal characteristics of sediment compaction and consolidation using geotechnical parameters collected from 152 boreholes, soil mechanics equations and the Kriging interplolation method. In addition, these estimates were partially constrained and cross-validated using the interferometric synthetic aperture radar (InSAR) results from early 2007 to late 2010 which were provided in a previous study. By performing a comparison analysis between theoretical evaluations of compaction for borehole data and InSAR observations, we were able to quantify subsidence due to sediment compaction. The comparison results suggest that the theoretical solutions agreed well with the measurements recorded by the well-validated, advanced InSAR method and that the deviations between the InSAR technique and geotechnical evaluations ranged from −22 to 3 mm. The results reveal that the land subsidence of the chosen borehole sites during the investigative period was dominated by the primary consolidation and compaction of sediment. The underprediction of subsidence may be explained by fluid withdrawal, oil exploitation and engineering construction. To speculate, more geological disasters may occur if the current subsidence condition extends into the future.